Southeast Asia in a New Era : Ten Countries, One Region in ASEAN - Hong, Mark; Thomson, Elspeth, 1960-; Severino, Rodolfo (Book collections on Project MUSE., 2010)
This book is about Southeast Asia in a new era. This new era began with a new century and a new millennium posing great challenges to the region and to each country in it. It has a chapter on each of the ten countries in the region, covering both the politics and the economic aspects. It has one on the region as a whole, and one on the Association of Southeast Asian Nations. It has a thoughtful afterword that is a summary of its contents but is more than the sum of the individual chapters. Ma ...